Perfil de rastreamento de resistência das Pseudomonas aeruginosa e acompanhamento da rotina educacional - Santos, Adailton Pereira dos (2018)
β-lactamases are enzymes that hydrolyze the β-lactam ring, inactivating the action of β-lactam antibiotics. The objective of this work was to diagnose phenotypically and molecularly 14 β- lactamase resistance genes expressed in Pseudomonas aeruginosa and to correlate the results found. A total of 99 samples of Pseudomonas aeruginosa were selected and the antibiogram was performed. Real-time PCR is being performed using the Sybr Green system to amplify the genes corresponding to the resistances found in phenotyping. Three/14 (21.4%) genes blaSME, blaOXA, blaGIM were found simultaneously in three samples. According to the statistical test, when evaluating the amplification results obtained for PPT, the molecular method was more sensitive for the detection of the gene coding for multidrug resistance, presenting values of (p <0.05). This information suggests that gene research is more sensitive and specific compared to the antibiogram.